ANALISIS PENDAPATAN USAHATANI ANTARA PETANI YANG MENGGUNAKAN BENIH PADI BERLABEL DAN BENIH PADI NON BERLABEL DI DESA LEPPANGANG KECAMATAN PATAMPANUA KABUPATEN PINRANG - Yusdi, Muhammad; -, Yusriadi; Sriwahyuningsih, A. Erna (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
The government has an inportant role in efforts to increase agricultural roductivity by giving great attention to developing seeds. One of the successes of efforts to increase rice production is very dependent on seeds quality, while quality seeds are labeled seeds, while farmers prefer to use non-labeled rice seeds rather than labeled rice seeds. This research is quantitative research using numerical data as a tool to analyze information about what you want to know. This research was conducted in Leppangang Patampanua Sub District, Pinrang District which starts from June to july 2018. The method used in this study is survey. The types of data collected are primary data and secondary data. The result of this study indicate (1) the amount of costs incurred between farmers who use labeled rice seeds and non-labeled rice seeds is significantly different, while the average cost of using rice seeds labeled is Rp. 8.284.046/period and non-labeled rice seeds of Rp.7.376.302/period. (2) the average income of farmers who use labeled rice seeds and non-labeled rice seeds in significantly different. For farmers who use rice seeds labeled as Rp. 23.101.512, while the income of farmers who use non-labeled rice seeds is Rp. 19.826.180. (3) R/C Ratio value farmers farms that use labeled rice seeds and non-labeled rice seeds are not significantly different from the 0,1. R/C Ratio of farmers who use labeled rice seeds = 3,79, whlie R/C Ratio of farmers who use non-labeled rice seeds = 3,69.